Aprovechamiento del mucilago de cacao (Theobroma Cacao L.) para la obtención de un néctar con cannabis no psicoactivo (Cannabis Sativa L.) - Sánchez Valero, Freddy Leandro (2024)
The rise of innovation in the food and beverage industry has led to the search for the revaluation of agricultural by-products such as cocoa mucilage, a viscous substance rich in sugars and nutrients, which used to be removed during the production of chocolate. Recent studies have shown that this material has an interesting potential in the manufacture of high value-added products. On the other hand, non-psychotropic hemp (Cannabis sativa L) is gaining weight in the market thanks to its therapeutic properties, being used in different personal care products and food supplements characterized by low THC and high CBD levels. The interest in adding non psychoactive cannabis to beverage production is mainly due to its health benefits, such as anti inflammatory and anxiolytic properties. By combining cocoa mucilage with cannabis extract, a very tasty and at the same time very functional nectar could be obtained. This proposal proposes that a healthy nectar could be the result of the combination of cocoa mucilage with non psychoactive cannabis extract that achieves a synergy with natural ingredients beneficial to human health at multiple levels. The mucilage contributes prebiotics, antioxidants and the hemp enriches the product with CBD, which has anxiolytic, neuroprotective and anti-inflammatory effects. This product has the potential to be used as a natural dietary supplement to promote relaxation, reduce stress and improve overall well-being